The Inflammatory Response to Miniaturised Extracorporeal Circulation: A Review of the Literature. (13th January 2010) - Vohra, Hunaid A.; Whistance, Robert; Modi, Amit; Ohri, Sunil K.
Abstract : Conventional cardiopulmonary bypass can trigger a systemic inflammatory response syndrome similar to sepsis. Aetiological factors include surgical trauma, reperfusion injury, and, most importantly, contact of the blood with the synthetic surfaces of the heart-lung machine. Recently, a new cardiopulmonary bypass system, mini-extracorporeal circulation (MECC), has been developed and has shown promising early results in terms of reducing this inflammatory response. It has no venous reservoir, a reduced priming volume, and less blood-synthetic interface. This review focuses on the inflammatory and clinical outcomes of using MECC and compares these to conventional cardio-pulmonary bypass (CCPB). MECC has been shown to reduce postoperative cytokines levels and other markers of inflammation. In addition, MECC reduces organ damage, postoperative complications and the need for blood transfusion. MECC is a safe and viable perfusion option and in certain circumstances it is superior to CCPB.